2022
DOI: 10.46656/access.2021.3.1(4)
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Georgia’s trade policy strategy: from frailty to sustainability

Abstract: The following article reviews the trade policies and practices of Georgia as well as Georgia-WTO relationship. The authors focus on Georgia's recent economic performance, including Association Agreement (AA) with the European Union that contributed powerfully to stabilising Georgia's trade legislation and reinforcing domestic economic reform. The Association Agreement between Georgia and the European Union and its member States aims at Georgia's gradual economic integration into the EU Internal Market, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It is concluded that it is not optimal for a very big bank to operate in a comparatively smaller national economy (Abuseridze et al, 2022). The European Banking Authority (2022) conducted an interesting study on the influence of the size of banks on some of their financial indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is concluded that it is not optimal for a very big bank to operate in a comparatively smaller national economy (Abuseridze et al, 2022). The European Banking Authority (2022) conducted an interesting study on the influence of the size of banks on some of their financial indicators.…”
Section: Literature Reviewmentioning
confidence: 99%